Deciphering role of technical bioprocess parameters for bioethanol production using microalgae - Farhana Bibi (Elsevier, 2021)
Microalgae biomass is considered an important feedstock for biofuels and other bioactive compounds due to its faster growth rate, high biomass production and high biomolecules accumulation over first and second-generation feedstock. This research aimed to maximize the specific growth rate of fresh water green microalgae Closteriopsis acicularis, a member of family Chlorellaceae under the effect of pH and phosphate concentration to attain enhanced biomass productivity. This study investigates the individual and cumulative effect of phosphate concentration and pH on specific growth characteristics of Closteriopsis acicularis in autotrophic mode of cultivation for bioethanol production. Central-Composite Design (CCD) strategy and Response Surface Methodology (RSM) was used for the optimization of microalga growth and ethanol production under laboratory conditions. The results showed that high specific growth rate and biomass productivity of 0.342 day−1 and 0.497 g L−1 day−1 respectively, were achieved at high concentration of phosphate (0.115 g L−1) and pH (9) at 21st day of cultivation. The elemental composition of optimized biomass has shown enhanced elemental accumulation of certain macro (C, O, P) and micronutrients (Na, Mg, Al, K, Ca and Fe) except for nitrogen and sulfur. The Fourier transform infrared spectroscopic analysis has revealed spectral peaks and high absorbance in spectral range of carbohydrates, lipids and proteins, in optimized biomass. The carbohydrates content of optimized biomass was observed as 58%, with 29.3 g L−1 of fermentable sugars after acid catalyzed saccharification. The bioethanol yield was estimated as 51 % g ethanol/g glucose with maximum of 14.9 g/L of bioethanol production. In conclusion, it can be inferred that high specific growth rate and biomass productivity can be achieved by varying levels of phosphate concentration and pH during cultivation of Closteriopsis acicularis for improved yield of microbial growth, biomass and bioethanol production.